Virtual reality exposure therapy as treatment for pain catastrophizing in Fibromyalgia patients : proof-of-concept - Morris, Linzette Deidre (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.